Molecular Studies of Membrane Interactions Using Probe Methods - Bashford, L (1975)
A biological membrane is a complex mixture of macromolecular components which performs a number of important physiological functions. These functions include the regulation of the chemical composition of the intramembrane space and the provision of a two dimensional support for a number of important enzymatic activities. In general membranes operate as discrete functional units and their various properties are uniquely integrated for optimal physiological activity. The work in this thesis was designed to explore the cooperative interactions of membrane components both at the physicochemical and biochemical levels. The particular experimental approach employed was the correlation of the properties of fluorescent probes bound to specific regions of the membrane with the particular biochemical properties of a number of membrane systems but principally of the bovine adrenomedullary chromaffin granule membrane. 1) Physicochemical Interactions in Membranes. Fluorescent probes were used to monitor the motional freedom in the membrane lipid phase. Biochemical studies and, in particular, the temperature dependence of a number of membrane-bound protein activities indicated that the properties of the membrane lipids might modulate the activities of the membrane proteins. Lipid fluidity is an important fea,ture of current thinking concerning membrane organisation. The membrane can be considered as a two dimensional viscous fluid with significant lateral mobility for many of its components. A series of different fluorescent probes were used in the experiments. This permitted the study of different regions of the lipid bilayer and helped to overcome the possible problems caused by the introduction of a perturbing impurity into the membrane. If a series of different probes all give essentially the same information it is difficult to argue that the phenomena arise solely because of the presence of the probe and it is much more likely to be an intrinsic property of the membrane. The probes used were 1-anilinonaphthalene-8-sulphonic acid and 2-(9-anthroyloxy)palmitic acid which bind close to the polar/nonpolar interface of the lipid bilayer, 12-(9-anthroyloxy)stearic acid which probes the region 1.5nm below the interface and the uncharged molecule N-pheiiyl-1-naphthylamine which binds to the hydrocarbon core of the membrane. The correct interpretation of the motional properties of fluorescent probes bound to natural membranes required a study of the probes' behaviour in well defined systems. It therefore proved necessary to study the properties of the probes incorporated into model membrane systems of known properties. In aqueous dispersions pure phospholipids exhibit a number of specific thermotropic effects. At a temperature defined by the head group and acyl chain structures such dispersions undergo an endotherrnic phase transition. The acyl chains in the bilayer move from a highly ordered, quasi-crystalline, gel state to a very fluid, disordered liquid crystalline state. In dispersions of dipalmitoyl lecithin this transition occurs at 41°C and was detected by all the probes used here. Characteristically the onset of the liquid crystalline phase is associated with an increase in the mobility of the fluorescent probes. The mobility of the probes was inferred by the measurement of their fluorescence polarisation and lifetime. For this purpose an instrument that monitored fluorescence polarisation and intensity (directly proportional to fluorescence lifetime) continuously with temperature was employed and changes in the probe mobility correlated with the known changes in the fluidity of the model system in question. It was possible to evaluate the use of fluorescence probes as monitors of phase transitions, phase separations and lipid clustering in defined systems. One particularly important observation made in the course of these studies was that fluorescent probes bound to phospholipid bilayers preferentially segregate into the most fluid regions of the bilayer in systems of mixed phase. Thus in a natural membrane one must expect the probes to bind to the most fluid region of the lipid bilayer. The information obtained from the model system studies was then used in the interpretation of the properties of the probes bound to natural membranes. In a number of cases involving widely different membrane systems the effects of temperature indicated that at low temperature significant lipid clustering or ordering occurred. The exceptions to this rule were the membranes derived from animals (crabs and lobsters) whose normal physiological temperature is quite low. The onset of lipid ordering correlated well with changes in the protein based activities of the membranes. For chromaffin granule membranes amd (Na+ + K+)-ATP ase containing membranes lipid ordering was associated with high activation energies for membrane-bound enzymes. In thyroid gland plasma membranes lipid ordering was associated with decreased specific hormone binding. Under conditions where lipid ordering is diminished (high temperature, presence of detergent or low ionic strength) enzyme activities have low activation energies and hormone binding capacity is increased. These studies indicate that there is a general correlation between lipid ordering and protein activity in biological mernbrpnes. This finding emphasises the point that membranes should be considered as an integrated functional unit, their various components interacting cooperatively with each other. This view means that studies only of membrane lipids or only of membrane proteins are liable to miss features characteristic of the whole membrane and that a proper understanding of the properties of biological membranes should encompass the properties of all the membrane components. 2) Biochemical Interactions in Membranes. The physicochemical integration of membrane structure and function is matched by the biochemical integration of membranes that perform a number of biochemical functions. The fluorescent probe 1-anilinonaphthalene-8-sulphonic acid reflects the state of energy-coupling (or biochemical integration) in the inner mitochondrial membrane. It was, therefore, used to explore the energy-coupling of the chromaffin granule membrane. These membranes catalyse the hydrolysis of ATP an activity associated with the active transport of catecholarrdnes. They also catalyse the hydroxylation of dopainine an important step in the biosynthosis of the catecholamines, noradrenaline and adrenaline. The ATPase activity is associated with the enhancement of the fluorescence of 1-anilinonaphthalene-8-sulphonic acid. The fluorescence response is abolished by mitochondrial uncoupling agents with a concomitant enhancement of the ATPase activity. Uncouplers also abolish active catecholamine transport in vesicles of chromaffin granule membranes. Other inhibitors such as reserpine, rotenone, oligomycin and antimycin A abolish active catecholamine transport but not the ATPase activity or the fluorescence response. They must, therefore, act at the level of the catecholamine carrier system. Inhibitors of the ATPase activity such as N-ethylmaleimide and dicyclohexylcarbodiimide also abolish active transport and the fluorescence response but do not affect catecholamine exchange across the membrane. These reagents, then, block the energy input to the system. A detailed analysis of the fluorescence response indicated that the enhancement could be entirely ascribed to increased probe binding and not to an altered quantum yield of the bound probe. The fluorescence enhancement caused by the imposition of an ionic diffusion potential induced by K+ flux in the presence of the ionophore valinomycin across the chromaffin granule membrane is associated with both binding and quantum yield changes. The response to ATP energisation is not, therefore, likely to be associated with changes in membrane potential. These results suggest that there might be en ATPase linked proton movement within or across the chromaffin granule membrane. A mechanism is proposed which may be the basis for the active transport of catecholamine and involves the enzyme linked proton movement as the energy requiring step. A detailed analysis of the pH dependence of the ATPase, the associated fluorescence response, the uncoupling of the fluorescence response end the passive binding of the probe suggest that one mechanism by which the granules retain their catecholamines is low pH (matrix pH appears to be about pH 5.5). Low pH also provides a suitable chemical environment for the catecholamines which are unstable and readily oxidised at pH values above 7.5. Finally the unusual anion distribution across the membrane (high levels of adenine nucleotid.es and acidic proteins are found in chromaffin granules) is discussed in terms of its contribution to the catecholamine storage mechanism. The conclusion is reached that the limited permeability of the membrane to cations, the low internal pH and the high levels of internal anions all contribute to the storage mechanism. It is pointed out that the rapid release of catecholamine from the medulla will require the breakdown of this highly organised storage system. One convenient method would be the removal of the limiting membrane which is, of course, a major feature of the exocytotic release mechanism proposed for the release of adrenomedullary catecholamines.